2022
DOI: 10.3390/cosmetics9040069
|View full text |Cite
|
Sign up to set email alerts
|

Methylcellulose-Chitosan Smart Gels for Hairstyling

Abstract: Methylcellulose and chitosan served as promising ingredients for a thermoresponsive hair styling gel after successful application in the medical industry. Both ingredients uphold the clean beauty standard without infringing on performance. By combining these two ingredients, a hair gel can be created that promises an extended hold of style once a heated external stimulus, such as a curling wand, is applied to the hair. Chitosan serves as the cationic biopolymer to adhere the gel to the hair, whereas the methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It is worth mentioning that chitosan continues to be explored for other hair applications such as styling gels due to its strong affinity for the hair surface. Hartson et al 164 showed that a composite based on chitosan and methylcellulose had excellent hair styling performance.…”
Section: Introducing Bio-based Compounds Into Cosmetic Formulations: ...mentioning
confidence: 99%
“…It is worth mentioning that chitosan continues to be explored for other hair applications such as styling gels due to its strong affinity for the hair surface. Hartson et al 164 showed that a composite based on chitosan and methylcellulose had excellent hair styling performance.…”
Section: Introducing Bio-based Compounds Into Cosmetic Formulations: ...mentioning
confidence: 99%